Physical base development for mathematical simulation of transmission process - Дорошенко, Олександр Іванович; Романюк, Олена Вікторівна; Борисенко, Світлана Олександрівна (Technology audit and production reserves, 2015)
Based on the physics of normal operation of power systems, in the article it is proposed new scientific and methodical approach to determining reactive power transmission systems to the power industry and customers equated to them, which is based on understanding the mains voltage as a potential form of electricity. That is why the generation and consumption of electricity in the same time and give it the properties of mobility and versatility. It is proposed realistic modeling of power, in which the mathematical calculations of the regime based on the physics of the process of power transmission technology. It is emphasized that electric networks at a voltage of 110 kV should be considered counter energy market and to establish a base (wholesale) price of electricity for each of its customers on the basis of the concept of its power from the 110 kV network system with the normative coefficient of reactive power transmission (tgφД).